Screening of Country Bean (Lablab Purpureus L.) Genotypes for Salinity Tolerance (Annals of Bangladesh Agriculture, 2023)
Thirty-five country bean (Lablab purpureus L.) genotypes collected from coastal belts of Bangladesh were screened for tolerance to a high level of salinity (12 ds m-1 NaCl) in Hogland nutrient solution in a hydroponic system at vegetative growth stage. The experiment was conducted in a complete randomized design with three replications at Genetics and Plant Breeding lab, BSMRAU during January-February, 2016. The genotypes were varied in biochemical properties (proline, carbohydrates, chlorophyll contents etc.), dry root: shoot ratio, relative shoot dry weight and salt susceptibility index (SSI). Wide variation among the genotypes was noticed for root and shoot ratio (p